2013
DOI: 10.1002/adma.201304667
|View full text |Cite
|
Sign up to set email alerts
|

Global and Local Superconductivity in Boron‐Doped Granular Diamond

Abstract: Strong granularity-correlated and intragrain modulations of the superconducting order parameter are demonstrated in heavily boron-doped diamond situated not yet in the vicinity of the metal-insulator transition. These modulations at the superconducting state (SC) and at the global normal state (NS) above the resistive superconducting transition, reveal that local Cooper pairing sets in prior to the global phase coherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 37 publications
9
53
2
Order By: Relevance
“…3). This is in steep contrast with previous studies on polycrystalline samples [11][12][13][14]. To our knowledge, such homogeneous hard gap was observed only in the case of a single crystal [15].…”
Section: O Onufriienko Et Alcontrasting
confidence: 99%
See 1 more Smart Citation
“…3). This is in steep contrast with previous studies on polycrystalline samples [11][12][13][14]. To our knowledge, such homogeneous hard gap was observed only in the case of a single crystal [15].…”
Section: O Onufriienko Et Alcontrasting
confidence: 99%
“…2, the superconducting gap in the density of states is gradually suppressed with increase of temperature and the estimated superconducting critical temperature T c = 7 ± 0.5 K. Such measurements were performed at numerous locations across the sample surface, yielding identical results within experimental error. We did not observe any spatial variation of SDOS as reported in previous studies of polycrystalline boron doped diamond [11][12][13][14]. Notably, the value of the differential conductance inside the superconducting gap is equal to zero (see Fig.…”
Section: O Onufriienko Et Alsupporting
confidence: 78%
“…Nanocrystalline diamond (NCD) thin films of a few tens to hundreds of nanometers thickness are a driver for fundamental as well as application‐oriented investigations exploiting the extreme properties of this material. The advantage of NCD is the possibility to cover large areas, however, the granular nature of NCD leads to properties based on the interplay between grains and grain boundaries . In doped films, grain boundaries provide a competing pathway for the incorporation of dopant atoms and thus questions have arisen on the efficiency of the in situ doping process in polycrystalline material.…”
Section: Introductionmentioning
confidence: 99%
“…Previous microstructural investigations using HRTEM and EELS techniques on the local B environment in HPHT polycrystalline diamond lms proposed that boron is present at the grain boundaries and in triangular shaped pockets at the grain junctions. 54,57 However, using the same EELS technique, in case of CVD deposited boron-doped polycrystalline diamond lms, Huang et al observed no signals from B at the grain boundaries and reported that the boron atoms are uniformly distributed inside each diamond grain.…”
Section: Boron-induced Levels Close To Valence Bandmentioning
confidence: 99%
“…Such inclusions were previously reported to be trapped in PC diamonds during their growth process. 57,58 With a bond dissociation energy of ca. 448 kJ mol À1 , the C-B bond once formed is much stronger than a C-H bond.…”
Section: Boron-induced Levels Close To Conduction Bandmentioning
confidence: 99%